High Levels of Resistance in A Culex quinquefasciatus Population to the Insecticide Permethrin in Filariasis Endemic Areas in Central Java - Chakim, Irfanul; Sayono,; Astuti, Rahayu (UI Scholars Hub, 2017)
Resistance among Culex mosquitoes to various insecticides has been reported in many countries. However, there have been no studies of the resistance status of Culex in Indonesia. There is a need for such studies to develop a database for use in vector control management. This study aimed to investigate the insecticide resistance status of C. quenquefasciatus, which is the primary vector of filariasis, to aid the planning of a vector control management program. In the present study, Culex quinquefasciatus larvae were collected from five districts/municipalities where filariasis is endemic in Central Java. The larvae were reared to adult stage, and insecticide susceptibility testing was then conducted according to standard bioassay procedures of the World Health Organization (WHO). The results of the bioassays showed that C. quinquefasciatus had a high level of resistance against 0.75% permethrin, with mortality rates ranging from 4.8 to 21.6%. The lowest resistance was found among mosquitoes collected from Grobogan district. This may be explained by the district’s remote geographical location. The high level of resistance found in the present study may be caused by exposure to local insecticides, which have been applied for many years as part of a dengue vector control program. These insecticides may also have contaminated the breeding sites of C. quinquefasciatus mosquitoes. Better vector control management is needed to help prevent the development and spread of resistance. Such management should include routine insecticide surveillance and insecticide alternation.